Optimalisasi Pembelajaran Aljabar Melalui Model Problem-Based Learning (PBL) Untuk Meningkatkan Hasil Belajar Peserta Didik - Sulistiyowati, Sri; Ernawati, Fetty (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2025)
Primary education plays a role in shaping the academic foundation and character of students, which is the main in mathematical subjects that are vital for logical and analytical development. However, mathematics is often a challenge for grade VII students, especially in understanding the concept of algebraic multiplication. Applying the problem-based learning (PBL) learning model is a solution to improve students' understanding and mathematical skills. This model is considered effective and easy to understand by students, so that it can make mathematics learning more interesting and know the learning outcomes of students. This study aims to determine the improvement of learning outcomes of grade VII students after applying the Problem-based learning (PBL) learning model to algebraic multiplication material. This research was carried out at MTs Negeri 2 Boyolali, Boyolali district, with 22 students in class VII B. This research uses the Classroom Action Research (PTK) motto which is compiled from four stages: planning, implementation of actions, observation, and reflexes. Data collection techniques are carried out through observation, tests, and documentation. The results of the study show that the problem-based learning (PBL) learning model can improve learning outcomes in algebraic multiplication with an average score of 56.5 in the first cycle and an increase in the second cycle with an average score of 79.5.